SOCIO-ECONOMIC DIMENSION OF FISH FARMING IN ASSAM - Sathiadhas, R.; Goswami, U. C.; Goswami, Mukunda; Ojha, S. N. (Journal of Indian Fisheries Association, 2015)
Information on socio-economic framework of the fishfarmer community forms a benchmark for policy formulation to develop this economically backward sector. Very few studies have been conducted on the socio-economic aspect of fish farming. Two districts of Assam, Darrang and Nagaon, were selected for this study where 120 respondents from each district were selected randomly. The characteristics representing the personnel and socio-economic attributes of the fishfarmers are presented in this paper. The socio-economic status of fish farmers has to be improved by bringing the modern concepts of fish farming to the doorstep of farmers. Keywords: Socio-economics, fish culture